Recovering value from waste: Development of G-Nanocellulose derived from ananas comosus leaves - Noor Ida Amalina, Ahamad Nordin; Gnanasekaran, Surenthiran; Jun Haslinda, Shariffuddin; Saidatul Shima, Jamari (2021)
Malaysia is known as one of the largest producers of pineapple in Asia, at the same time it created a large quantity of waste; Pineapple leave fibre (PALF) is the main waste of this industry. Due to lack of study in agricultural waste management, Normally, PALF is left on the plantation for nutrient cycling or being burnt, and this circumstance may lead to air pollution. PALF possess higher cellulose (81.27%) content; lower lignin (3.46%) content than other natural fibre.